Competition Law and Policy in Switzerland - Gugler, Philippe (OECD Publishing, 2007)
Swiss competition policy has traditionally been relatively lenient and low profile. The impact of competition policy on economic development has therefore been at best neutral. As the slow rate of growth becomes an issue, however, a more vigorous approach to competition has been identified as an important factor for improving growth prospects. The 2003 reform of the Cartel Act strengthened Swiss competition law, in particular by introducing direct sanctions for the most serious infringements and a leniency programme, thus bringing it closer to that of the European Union and of many other OECD countries. The Swiss Competition Commission has been given considerable new powers to combat private restraints of competition. Comco will have to enforce the new laws resolutely and step up action to promote regulatory reforms. In doing so, it is burdened by institutional arrangements and mechanisms that temper its full independence. The Swiss competition enforcers do not benefit from the networks of exchanges available to national competition authorities in EU member States. Matters are further complicated by a relative lack of resources. Strengthening competition is key for an effective internal market. The amendments to strengthen the Cartel Law and pending reform proposals signal determination on the part of the Confederation to tackle the problems. This report served as the basis for a peer review in the Competition Committee in 2005
Keywords: Governance; Switzerland